A 44μW Two-Electrode ECG Acquisition ASIC with Hybrid Motion Artifact Removal and Power-Efficient R-Peak Detection - Qu, Tianxiang; Yang, Xuecheng; Tang, Biao; Li, Xiao; Chen, Min; Hong, Zhiliang; Zeng, Xiaoyang; Xu, Jiawei (IEEE transactions on biomedical circuits and systems, 2025)
Motion artifacts (MA), common-mode interference (CMI), and varying electrode-tissue impedance (ETI) are the main factors that cause heart rate detection errors in practical wearable ECG acquisition. These problems are further exacerbated in two-electrode based ECG systems. This article presents an ambulatory ECG acquisition ASIC with fully integrated, low power motion artifacts removal (MAR) and heart rate detection, specifically for two-electrode ECG measurement. To alleviate the significant CMI due to the absence of subject bias electrode, this work utilizes an improved common-mode cancellation scheme to suppress CMI up to 40V pp with dynamic power consumption. To address excessive MA caused by the body movement, a hybrid MAR technique is proposed, where both ETI and DC electrode offset (DEO) signals are incorporated as inputs to the adaptive filter. This approach not only prevents channel saturation in a power-efficient manner, but also accurately extracts MA and suppresses it in real time, thereby ensuring stable ECG outputs and accurate, power-efficient R -peak detection even in the presence of body movements. Fabricated in a standard 180nm CMOS process, the core IA achieves an input referred noise (IRN) of 0.62μV rms (1-150Hz), an input impedance of 1.9GΩ and a total-CMRR (T-CMRR) of 92dB at 50Hz. In a two-electrode configuration, the ASIC successfully suppresses the MA and obtains a high-quality ECG with well-identified QRS complex, enabling the built-in R -peak detection algorithm to calculate real-time heart rate more accurately and efficiently.